The Role of Top Management Leadership in Adopting TQM Values: Using Kurt Lewin’s Change Approach to Create and Sustain TQM - ZEID, Djaber; SAADI, Imad; KHALLOUT, Djihed (Finance and Business Economies Review, 2019)
This paper aims at exploring how Top Management Leadership (TML) can act in order to adopt the appropriate values for Total Quality management (TQM) in the organizations. Kurt Lewin‘s change approach was proposed for TML as a useful process to evaluate, change and sustain the necessary values for TQM. Each stage of Lewin‘s model requires TML to provide necessary tools and methods in order to keep the operation of adopting TQM values on the right track.